Forecasting Red Cayenne Chili Prices to Maintain Inflation Stability in West Nusa Tenggara - Masani, Sab'ul; Raisa, Daeva Mubarika; Suryaningrum, Dyah Ayu; Nasution, Ade Rezkika; Swarli, Yousf Bellin (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Inflation is a key challenge in economic management because it directly influences purchasing power, living costs, and price stability. In West Nusa Tenggara Province, red cayenne pepper is a volatile food commodity and a major contributor to regional inflation due to sharp price fluctuations and high consumption. This study aims to develop a price forecasting model for red cayenne pepper using the Triple Exponential Smoothing (Holt–Winters) method, which accounts for level, trend, and seasonal components to reflect dynamic price movements. The study uses monthly red cayenne pepper price data from January 2022 to June 2025 sourced from the National Food Agency. Descriptive analysis is applied to identify price characteristics and movement patterns, while inferential analysis is used to estimate the forecasting model. The smoothing parameters α, β, and γ are optimized using EViews and Microsoft Excel to determine the best model specification. The results show that the optimal parameters are α = 0.1, β = 0.3, and γ = 0.3. The model successfully captures seasonal price behavior and achieves a Mean Absolute Percentage Error (MAPE) of 37.54% and a Root Mean Squared Error (RMSE) of 25,557.5, indicating acceptable forecasting performance for a volatile commodity. Forecasts for July 2025 to June 2026 indicate substantial price variability, with the lowest projected price occurring in October 2025 at IDR 58,862.32 per kilogram and the highest in March 2026 at IDR 145,004.93 per kilogram. Seasonal patterns reveal price declines during peak harvest periods and sharp increases during supply shortages.